Persuasive technology designing for future change : 15th International Conference on Persuasive Technology, PERSUASIVE 2020, Aalborg, Denmark, April 20-23, 2020, Proceedings /: designing for future change : 15th International Conference on Persuasive Technology, PERSUASIVE 2020, Aalborg, Denmark, April 20-23, 2020, Proceedings. (2020) - Unknown
No abstract available